Experiments and CFD simulation of a biomass cookstove for combustion efficiency improvement at various air conditions - Umer Hayyat; Suraj S. Ghiwe; Muhammad Shahid; Muhammad Usman Khan; Muhammad Sultan; Muhammad Aleem; Shohreh Azizi; Muhammad Farooq; Fahid Riaz (Case Studies in Thermal Engineering)
Cooking is an essential household activity, and as natural gas and LPG prices rise, there is a growing demand for alternative cooking methods. The current study combines CFD and experimental analysis to investigate how air velocity and distribution affect combustion efficiency in biomass cookstoves. A swirl flow model is developed to investigate the effect of air velocity on the thermal efficiency and water boiling time of a biomass cookstove. The experimental analysis varies the air velocity (0.5 m/s, 0.75 m/s, and 1 m/s) to see how it affects combustion efficiency. Computational simulations are carried out concurrently to model the air distribution inside the cookstove and how it affects the combustion process. The results reveal that the developed biomass cookstove showed promising results at an air velocityof 1 m/s. Also, compared to straight flow, the swirl flow air distribution in biomass cookstoves increased the thermal performance of the cookstove by 11 %. Findings indicate that the developed biomass cookstove achieved a Tier 3 rating with a thermal efficiency of 32 % at optimized conditions.